SPEED ANALYSIS ON SAFE SCHOOL ZONES (ZOSS): CASE STUDY OF PANYINGKIRAN-MAJALENGKA ROAD - Renaldi Agustian; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2024)
Road safety is in the interest of every driver and the community around the road. Drivers often exceed speed limits and violate traffic signs. This issue has always been at the core of the world's roads. Zona Selamat Sekolah (ZoSS) didesain agar kendaraan yang melewati daerah ZoSS berada dalam kecepatan rendah (maksimal 30 km/jam). Speed seriously impacts the safety of drivers and other road users. In the province of West Java, many still ignore speed on certain roads, which is one of the causes of accidents. One often ignored is the Panyingkiran-Majalengka road, a major road with several schools. The type of research used is quantitative research with descriptive methods, which describe the speed facts at the research location. The data needed in this study are primary data, where primary data is data that is directly obtained in the field (km/h) at the research location. Several measurements can measure speed including Time Mean Speed, Running Speed, Journey Speed, and Spot Speed. The speed of vehicles on Monday-Wednesday is between 28 and 36 km/h, with an average speed of 32 km/h. Meanwhile, the speed of each vehicle ranged from 27-40 km/h with an average speed of 34 km/h. From the field survey results, the ZoSS markings and speed limit signs are not visible. The cause of the high speed in the Safe School Zone is the lack of supporting facilities such as road markings and signs.